Request of use of BRACU supplied cement/rebar for some works other than BOQ items - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request of use of cement or rebar supplied by BRACU for some works other than BOQ items for BRACU new campus project.